2016
DOI: 10.3390/ijms17091392
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Signal Output and Avoiding BOD/Toxicity Combined Shock Interference by Operating a Microbial Fuel Cell Sensor with an Optimized Background Concentration of Organic Matter

Abstract: In the monitoring of pollutants in an aquatic environment, it is important to preserve water quality safety. Among the available analysis methods, the microbial fuel cell (MFC) sensor has recently been used as a sustainable and on-line electrochemical microbial biosensor for biochemical oxygen demand (BOD) and toxicity, respectively. However, the effect of the background organic matter concentration on toxicity monitoring when using an MFC sensor is not clear and there is no effective strategy available to avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 20 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…The study revealed that the background organic matter concentration should be fixed at a high level of oversaturation for maximizing the signal output when the ‘ ∆I ’ is selected relative to the concentration of a toxic agent. On the other hand, IR should be fixed to a lower value near to the detection limit to maximize the signal output . The results of this study are shown in Figure .…”
Section: Microbial Fuel Cells As Biosensorsmentioning
confidence: 97%
See 2 more Smart Citations
“…The study revealed that the background organic matter concentration should be fixed at a high level of oversaturation for maximizing the signal output when the ‘ ∆I ’ is selected relative to the concentration of a toxic agent. On the other hand, IR should be fixed to a lower value near to the detection limit to maximize the signal output . The results of this study are shown in Figure .…”
Section: Microbial Fuel Cells As Biosensorsmentioning
confidence: 97%
“…Recently, Yong et al . studied the effect of organic matter concentration (in anode) on toxicity monitoring to avoid the signal interference by the combined shock of BOD and toxicity . The study revealed that the background organic matter concentration should be fixed at a high level of oversaturation for maximizing the signal output when the ‘ ∆I ’ is selected relative to the concentration of a toxic agent.…”
Section: Microbial Fuel Cells As Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is apparent therefore that MFCs respond to many toxic substances, but the magnitude of the response depends on the concentration and inherent toxicity of any particular compound. Importantly, using the MFC-based toxicity sensors reported to date there, are difficulties in distinguishing a drop in sensor output caused by a drop in BOD levels from a drop in sensor output caused by the presence of a toxic compound (Kim et al, 2006b;Jiang et al, 2016;Tan et al, 2018). There is therefore a clear need for the development of a sensor capable of distinguishing between BOD and toxicity detection.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the microbial fuel cell (MFC) based sensor has attracted growing interest because it can achieve self-sustainable and low-cost water monitoring without additional transducers, power sources or specialty chemicals [2][3][4][5]. The bioanode of an MFC is generally used as the sensing and transducing element, at which electrogenic microorganisms oxidize the organic substrate and release protons and electrons [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%